Revisiting Remissions Policy for Corruption Offenders: A Siyāsah Tasyrī'iyyah Analysis of Law No. 22 of 2022 - Nimah, Rodhotun; Kamsi, Kamsi; Tahir, Achmad (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2023)
Law No. 22 of 2022 on Corrections is a legal reform that replaces Law No. 12 of 1995. Before the enactment of this law, correctional regulations were governed by several rules, including Government Regulation No. 99 of 2012, Ministry of Law and Human Rights Regulation No. 3 of 2018, and Ministry of Law and Human Rights Regulation No. 7 of 2022. However, in practice, Law No. 22 of 2022 still leaves unresolved issues of inconsistency with the principles and objectives of the state, particularly regarding the substance of granting remission to corrupt prisoners. This article examines these regulations from the perspective of siyāsah tasyrī’iyyah and assesses their relevance to anti-corruption efforts. The research uses a normative legal method with a legislative approach, utilizing the theory of siyāsah tasyrī’iyyah and legislative theory. The research results indicate that the rules on remission for corrupt prisoners only partially fulfill the principles of siyāsah tasyrī’iyyah, namely the principle of gradualism in enacting laws and simplifying regulations. Meanwhile, the principles of ease, public interest, and justice have not been realized. Based on Article 28 of the 1945 Constitution, human rights can indeed be restricted by law, so the restriction of remission for corrupt prisoners is considered valid. Therefore, Article 10 of Law No. 22 of 2022 must be revised. Undang-Undang Nomor 22 Tahun 2022 tentang Pemasyarakatan hadir sebagai pembaruan hukum yang menggantikan Undang-Undang Nomor 12 Tahun 1995. Sebelum lahirnya undang-undang tersebut, aturan pemasyarakatan ditetapkan melalui beberapa regulasi, antara lain PP Nomor 99 Tahun 2012, Permenkumham Nomor 3 Tahun 2018, dan Permenkumham Nomor 7 Tahun 2022. Namun, dalam praktiknya, Undang-Undang Nomor 22 Tahun 2022 masih menyisakan problem ketidaksesuaian dengan asas dan tujuan negara, terutama terkait substansi pemberian remisi bagi narapidana korupsi. Artikel ini membahas pengaturan tersebut dalam perspektif siyāsah tasyrī’iyyah dan menelaah relevansinya terhadap upaya pemberantasan korupsi. Penelitian menggunakan metode hukum normatif dengan pendekatan perundang-undangan, serta memanfaatkan teori siyāsah tasyrī’iyyah dan teori legislasi. Hasil penelitian menunjukkan bahwa aturan remisi bagi narapidana korupsi hanya memenuhi sebagian prinsip siyāsah tasyrī’iyyah, yaitu prinsip berangsur-angsur dalam penetapan hukum dan prinsip penyederhanaan peraturan. Sementara prinsip kemudahan, kemaslahatan, dan keadilan belum terwujud. Berdasarkan Pasal 28 UUD 1945, hak asasi manusia memang dapat dibatasi oleh undang-undang, sehingga pembatasan remisi bagi narapidana korupsi dinilai sah. Oleh karena itu, Pasal 10 UU No. 22 Tahun 2022 dipandang perlu untuk direvisi.